Intravenous Delayed Gadolinium-Enhanced MR Imaging of the Endolymphatic Space: A Methodological Comparative Study - Boegle, Rainer; Gerb, Johannes; Kierig, Emilie; Becker-Bense, Sandra; Ertl-Wagner, Birgit; Dieterich, Marianne; Kirsch, Valerie (Frontiers in Neurology, 2021)
In-vivo non-invasive verification of endolymphatic hydrops (ELH) via intravenous delayed Gadolinium (Gd) enhanced magnetic resonance imaging of the inner ear (iMRI) is rapidly developing into a standard clinical tool to investigate peripheral vestibulo-cochlear syndromes. In this context, methodical comparative studies providing standardization and comparability between labs seem all the more important, yet remain sparse. This study examined 108 participants, 75 patients with Meniere’s disease (MD; 55.2 ± 14.9 years) and 33 vestibular healthy controls (HC; 46.4 ± 15.6 years). The aim was to understand (i) how variations in acquisition protocols influence endolymphatic space (ELS) MR-signals; (ii) how therefrom ELS quantification methods correlate to each other or clinical data; and finally, (iii) how ELS extent influences MR-signals. Diagnostics included neurootological assessment, video-oculography during caloric stimulation, head-impulse test, audiometry, and iMRI. Data analysis provided semi-quantitative (SQ) visual grading and automatic algorithmic quantitative segmentation of ELS area [2D, mm2] and volume [3D, mm3] using a deep learning based segmentation of the inner ear’s total fluid space (TFS), and volumetric local thresholding. As a result, within the range of 0.1 to 0.2 mmol/kg Gd dosage and a 4 h ± 30 min time delay, SQ grading and 2D- or 3D- quantifications were independent of signal intensity (SI) and signal-to-noise ratio (SNR)(FWE corrected, p<0.05). Used ELS quantification methods were highly reproducible across raters or thresholds and correlated strongly (0.3- 0.8). However, 3D-quantifications showed least variability. Asymmetry indices and normalized ELH proved to be most useful for predicting quantitative clinical data. ELH size influenced SI (cochlea basal turn p<0.001), but not SNR. SI could not predict the presence of ELH. In conclusion, 1) Gd dosage of 0.1 to 0.2 mmol/kg after 4h±30 min time delay suffices for ELS quantification. 2) An agreed upon clinical SQ grading classification including a standardized level of evaluation reconstructed to anatomical fixpoints is needed. 3) 3D-quantification methods of the ELS are best suited for correlations with clinical variables, should include both ears and ELS values reported relative or normalized to size. 4) ELH increases signal intensity in the basal cochlear turn weakly, but cannot predict the presence of ELH.